Multi-Omics Integration for Advancing Microbial Bioremediation: PRISMA-Based Systematic Review - Ernawati, Ernawati; Hala, Yusminah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bioremediation is a sustainable approach to environmental restoration; however, its effectiveness is often constrained by limited understanding of molecular mechanisms and complex microbial interactions. This study aims to systematically review the transformative role of integrated multi-omics approaches including genomics, transcriptomics, proteomics, and metabolomics in enhancing bioremediation efficiency. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines across 10 empirical studies published between 2019 and 2024. Data were collected from Scopus, Web of Science, and PubMed databases using the keywords “bioremediation,” “multi-omics,” “microbial interactions,” and “environmental restoration.” Data analysis employed a qualitative thematic synthesis approach to identify key patterns and contributions. The findings reveal that multi-omics integration enables the elucidation of key catabolic pathways, identification of critical degradative enzymes, and characterization of synergistic microbial dynamics that drive pollutant degradation. Furthermore, integrating multi-omics data facilitates the rational design and engineering of synthetic microbial consortia with significantly improved bioremediation performance. In conclusion, the multi-omics framework represents a paradigm shift from descriptive to predictive and engineering-based bioremediation, providing a strong scientific foundation for more precise and sustainable environmental recovery strategies.